Clinical Appropriateness of Serum Folate ordering pattern in a tertiary care hospital in Saudi Arabia - Husain Y. Alkhaldy; Mohammed Alqahtani; Zainab S. Alamri; Nuha A. Althibait; Meteb A. Ahmed; Mohammed A. Alzahrani; Omayma S. Bakheet; Shahid Aziz (Elsevier, 2020)
Folate, also known as vitamin B9, is a co-factor necessary for DNA synthesis. Folate deficiency is associated mainly with hematological findings including megaloblastic anemia and pancytopenia. Many countries have mandated grain fortification with micronutrients including folic acid resulting in a reduced prevalence of folate deficiency. Saudi Arabia imports most of the grain products and folate is usually added after milling. There are no local studies to address the folate deficiency prevalence. In this study we aimed to analyse the clinical appropriateness of ordering practice of serum Folate level. Method: We reviewed all serum folate requests received at our laboratory in Aseer Central Hospital over one-year period (July 2018 June 2019). We collected patients' demographics from the electronic requests along with biochemical results of serum B12, ferritin and CBC results. We assessed appropriateness of orders against pre-specified criteria and applied statistical tests to explore for any association or significance. Results: Serum folate requests from 614 patients were received during the study period. Serum B12 (543, 88%), and serum ferritin (511, 83%) were concurrently requested. The most common reason for request, when available, was anemia. Anemia was present in (313, 51%) of the subjects for which microcytic anemia was predominant (199, 63.5%), followed by normocytic anemia (101, 33%) and only 10 subjects had macrocytic anemia (3.2%). The most common hematinics' deficiency was ferritin (30%) followed by B12 (17.2%). Serum folate deficiency was low, observed in only 2.8%. Low folate levels were not significantly different between the group with anemia and the normal hemoglobin group. Conclusion: This study identifies a commonly inappropriate serum folate ordering practice that includes ordering all hematinics at the same visit without considering the possible anemia etiologies. The excessive requests might be related to doctors attempt to avoid multiple blood extractions and to try to reduce the time for diagnosis. These policies are generating unnecessary costs and time loss. Education, phasing out or restricting some tests and introducing laboratory policies like sample storing could help reduce unnecessary requests.